Tropical savanna conversion to exotic pastures negatively affects taxonomic and functional diversity of dung beetle assemblages, but not dung removal - Maciel, Rafaella (2023)
1. The replacement of natural systems with agricultural lands is the main factor resulting in land use change in tropical regions. Tropical savannas cover more than 20% of the global land surface, and one-fifth of the world's population depends directly on these systems. 2. Here, we aim to understand how the conversion of tropical savanna into exotic pastures affects the taxonomic and functional metrics of communities and dung removal, using dung beetles as a focal group in a biodiversity hotspot—the Brazilian Cerrado biome. We used species richness, abundance, total biomass, and species composition as assemblage metrics, and functional richness, equitability and dispersion indices, and functional composition as functional diversity metrics. 3. The replacement of native savanna with exotic pastures negatively affected taxonomic and functional metrics, suggesting a simplified system where some disturbance-tolerant species become dominant. However, the relationship between dung removal and functional richness was higher in pastures compared to savanna. 4. Our results demonstrated that responses of dung beetle assemblages and dung removal to land use changes are decoupled, idiosyncratic and context-dependent, presenting challenges for making predictions and generalisations about the effects of land use change on ecological processes mediated by animals.